Vertical Patterns of Soil Bacterial and Fungal Communities along a Soil Depth Gradient in a Natural Picea crassifolia Forest in Qinghai Province, China - Hu, Lei; Wang, Xin; Song, Xiaoyan; Dai, Di; Ding, Luming; Degen, Abraham Allan; Wang, Changting (Forests, 2023)
Soil bacterial and fungal communities play different roles in maintaining the ecosystem structure and functions. However, these differences, which are related to soil depths, remain unclear and are the subject of this study. We selected six sample plots (20 m × 50 m) in a natural Picea crassifolia forest in an alpine meadow to determine the vertical patterns (0~10 cm, 10~20 cm, 20~30 cm, and 30~50 cm) of soil bacterial and fungal communities, and to predict their potential functions. The phyla Verrucomicrobia, Acidobacteria, and Proteobacteria dominated the soil bacteria, with more than 50% of the relative abundance, while the fungi Basidiomycota and Ascomycota dominated the soil fungi. The potential functions of bacteria, including metabolism and transcription, increased with soil depth, and corresponded to specific bacterial taxa. The functional guilds of fungi, including endophytes, arbuscular mycorrhiza, and ectomycorrhiza, did not change with soil depth. The structural equation modeling analysis revealed that soil organic carbon (SOC) and pH were the key drivers shaping the soil bacterial communities and potential functions in the 0–50 cm soil layer. SOC was also a key driver of soil fungal α diversity. The sample plot, namely, its geographic locations, was another key driver shaping soil fungal β diversity and potential functions, but soil depth was not. Our results differentiate the importance of SOC and geographic location in shaping soil bacterial and fungal communities, respectively, and indicate that examining soil microbial composition and corresponding functions concomitantly is important for the maintenance and management of forest ecosystem functions.